2016
DOI: 10.3748/wjg.v22.i46.10093
|View full text |Cite
|
Sign up to set email alerts
|

Can probiotics benefit children with autism spectrum disorders?

Abstract: Children with autism are commonly affected by gastrointestinal problems such as abdominal pain, constipation and diarrhea. In recent years, there has been a growing interest in the use of probiotics in this population, as it hypothetically may help to improve bowel habits and the behavioral and social functioning of these individuals. The gut microbiome plays an important role in the pathophysiology of organic as well as functional gastrointestinal disorders. Microbial modification with the use of antibiotics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 109 publications
0
88
0
6
Order By: Relevance
“…Studies have also reported altered gastrointestinal motility and increased intestinal permeability in ASD (D'Eufemia et al, 1996;Boukthir et al, 2010;de Magistris et al, 2010), which may increase the risk of translocation of bacteria or neurotoxic peptides, such as lipopolysaccharide (LPS). However, inconsistency is again observed (Navarro et al, 2016).…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have also reported altered gastrointestinal motility and increased intestinal permeability in ASD (D'Eufemia et al, 1996;Boukthir et al, 2010;de Magistris et al, 2010), which may increase the risk of translocation of bacteria or neurotoxic peptides, such as lipopolysaccharide (LPS). However, inconsistency is again observed (Navarro et al, 2016).…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 96%
“…Some studies found an association between gastrointestinal symptoms and severity of ASD symptoms (Adams et al, 2011;Wang L. W. et al, 2011;Mazurek et al, 2013), but others could not reproduce these findings (Kang et al, 2013;Son et al, 2015). ASD patients appear to have a higher prevalence of IBD (Doshi-Velez et al, 2015) and a higher number of pro-inflammatory immune cells in the intestinal wall (Navarro et al, 2016), although intestinal inflammatory markers, such as fecal calprotectin, appear normal (Navarro et al, 2016). The gastrointestinal symptoms may be caused by the presence of more pro-inflammatory gut bacteria (Fattorusso et al, 2019), but other factors may also be involved (Mayer et al, 2014).…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 99%
“…Probiyotikler, bağırsak mikrobiyatasını olumlu yönde etkileyebileceği ve otizmli çocuklarda potansiyel olarak zararlı metabolitlerin seviyelerini değiştirebileceğine dair teoriler bulunmaktadır. Probiyotiklerin davranış ve bu belirteçler üzerine etkileri henüz doğrulanmamıştır (19).…”
Section: Otizmunclassified
“…A useful source of information regarding this issue lies on autism research, given that ASD patients commonly suffer from gastrointestinal symptoms and intestinal microbiota imbalance characterized by low‐grade intestinal inflammation and increased gut permeability . Multiple studies have shown a distinct phylogenetic composition of gut microbiota in ASD patients compared to typically developing individuals, which is identified by increased Firmicutes/Bacteroidetes ratio, low levels of Actinobacteria, Proteobacteria, and Bifidobacteria and overgrowth of Clostridium and Sutterella species . The majority of these studies were cross‐sectional and involved subjects beyond toddlerhood; as autism‐related behavioral and sensory abnormalities commonly lead to disturbed eating patterns and restricted diets, the question whether intestinal microbiota imbalance is a cause or a consequence of autism spectrum disorders cannot be answered.…”
Section: The Role Of Gut‐microbiota In Autism‐related Social Deficitsmentioning
confidence: 99%
“…However, most relevant studies have small sample sizes and methodological weaknesses including the use of parent‐reported measures and a lack of clarity of ASD diagnostic criteria. In line with these observations, a recent review on the topic concluded that there is not adequate evidence and further research is warranted . There is a promising double‐blind randomized controlled study underway, focusing on the effect of a prebiotic regimen on ASD toddlers’ and preschoolers’ gastrointestinal, behavioral, language, and cognitive symptoms, and its results are anticipated with great interest .…”
Section: The Role Of Gut‐microbiota In Autism‐related Social Deficitsmentioning
confidence: 99%